Molecular Aggregation of Naphthalene Diimide(NDI) Derivatives in Electron Transport Layers of Inverted Perovskite Solar Cells and Their Influence on the Device Performance. Issue 1 (28th November 2019) - Liu, Wenbo; Shaikh, Dada B.; Rao, Pedada Srinivasa; Bhosale, Rajesh S.; Said, Ahmed Ali; Mak, Adrian M.; Wang, Zongrui; Zhao, Mu; Gao, Weibo; Chen, Bingbing; Lam, Yeng Ming; Fan, Weijun; et al.
Abstract: One of key factors to design applicable electron transport layers (ETLs) for perovskite solar cells is the morphology of ETLs since a good morphology would help to facilitate the carrier transport at two interfaces (perovskite\ETL and ETL\cathode). However, one drawback of most organic ETL small molecules is the internal undesired accumulation, which would cause the formation of inappropriate morphology and rough ETL surface. Here, by elaborately designing the side chains of NDI derivatives, the molecular interaction could be modified to achieve the aggregation in different degrees, which would eventually affect the accumulation of molecules and surface qualities of ETLs. By speculating from the comparison between the absorption spectra of solutions and films, the sequence of extent of molecule interaction and aggregation was built among three NDI derivatives, which is further confirmed by direct evidence of atomic force microscopy (AFM) images. Then, carrier exaction abilities are simply studied by steady‐state photoluminescence spectroscopy. The carrier transport process is also discussed based on cyclic voltammetry, time‐resolved photoluminescence spectroscopy and mobility. NDIF1 are proven to have the appropriate internal aggregation to smooth the contact with cathode and low series resistance, and a device performance of 15.6 % is achieved. With the ability of preventing the thermal diffusion of Ag towards the perovskite surface due to the strong interaction between molecules, NDIF2 at high concentration shows the highest fill factor (80 %). Abstract : Three naphthalene dimide (NDI) derivatives have been synthesized and are found to achieve different molecular interactions, aggregations and morphologies on the perovskite surface. Different extent of molecular aggregations and morphology features are demonstrated to have a great influence on the J sc and fill factors of those NDI derivative‐based perovskite solar cells.